Cuprophilic interactions in highly luminescent dicopper(i)–NHC–picolyl complexes – fast phosphorescence or TADF?. Issue 14 (4th January 2016) - Nitsch, Jörn; Lacemon, Frederick; Lorbach, Andreas; Eichhorn, Antonius; Cisnetti, Federico; Steffen, Andreas
Abstract : Cuprophilic interactions can greatly enhance the radiative rate constants via either exceptionally fast phosphorescence or TADF, and thus present a design motif for highly efficient Cu I -based emitters. Abstract : This case study on a series of monomeric, dimeric and polymeric Cu I chlorido NHC–picolyl complexes shows that cuprophilic interactions can ensure strong spin–orbit coupling for fast (reverse)intersystem-crossing T1 ↔ S1 and T1 → S0, and therefore can serve as a design motif for the construction of highly efficient Cu I -based TADF or T1 emitters.